Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.soscij.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

On the supply of China's healthcare resources in a decentralized healthcare system

Abstract: The structure of China's current governance bears prominent features of fiscal decentralization. The supply of healthcare resources in China has clearly witnessed slower growth in the last two decades during which the fiscal decentralization process has taken place. Using China's provincial panel data, we examine the determinants of healthcare resource supply while paying particular attention to the role of fiscal decentralization. We find that the supply of healthcare resources is inversely related to the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…The higher the per capita GDP means a better economic status of an individual province. Generally, a higher level of the economy suggests that the province has priorities in the allocation of health resources and therefore has a better chance of realizing the full utilization of health resources, which would promote the efficiency of the medical service system [ 69 ]. Furthermore, a better development of economy is usually accompanied by a higher level of technology, more research and development investments, which might indirectly promote the growth of efficiency of medical service systems [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher the per capita GDP means a better economic status of an individual province. Generally, a higher level of the economy suggests that the province has priorities in the allocation of health resources and therefore has a better chance of realizing the full utilization of health resources, which would promote the efficiency of the medical service system [ 69 ]. Furthermore, a better development of economy is usually accompanied by a higher level of technology, more research and development investments, which might indirectly promote the growth of efficiency of medical service systems [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…This situation has exacerbated the contradiction between resource space allocation and service utilization. Due to the fiscal decentralization system, local governments have reduced healthcare investment [51] ,fiscal transfer payment methods and government budgetary expenditures have become the main ways to improve the allocation of healthcare resources [52] [53] .In recent years, the higher-level government creatively uses the financial transfer payment method, the basic rigid regulations and subsidies for local governments to increase healthcare investment have enabled the level of resource allocation of primary healthcare institutions to be improved. The study found that the impact of economic indicators on the coupling coordination of primary healthcare institutions began to be significant at the 0.1% level in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The medical service utilization research mainly discusses the bed utilization rate of different levels of health institutions [20] , urban and rural residents' medical service utilization preference [21] and inequality issues [22] . In terms of factors influencing the equity of healthcare resources allocation, local economic level [23] , demographic characteristics [24] , decision-making mechanism [25] , terrain conditions [16] , information asymmetry and adverse selection [26] are considered to be the main factors. In terms of factors influencing the equity of utilization of healthcare services, demographic characteristics [ 27 ] , urban-rural differences [ 28 ] , institutional equity, income levels [ 29 ] , and medical insurance [ 30 ] are considered to be the main factors.However, there is still a lack of quantitative analysis of the relationship between healthcare resources allocation and service utilization.So what is the relationship between the allocation and utilization of healthcare resources in China; how is this relationship evolving; whether there is a spatial inequity or not; how is this relationship affected by the influencing factors of healthcare resources allocation and service utilization, there is still no reasonable answer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they examine significant positive spillover growth shocks to other counties, which suggests that counties whose neighbour grow faster than expected, to grow faster than expected. Zheng, et al (2013) took 21 province data (from time period [1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006] to investigate the supply of healthcare expenditures, which causes to slow down economic growth from last two decades. They use spatial panel data econometrics and find that the supply of healthcare resources is negatively related to the degree of decentralisation.…”
Section: Decentralisation Economic Growth Spillover Effects and Spamentioning
confidence: 99%